Isolation and characterization of spore-forming bacilli pathogenic for mosquito larvae in Java - Sugeng Juwono Mardihusodo, Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
The use of chemical insecticides for controlling mosquito vector of diseases has resulted in a lot of negative impacts. The objective of this study was to search for spore-forming bacilli effective as larvicides for prospective production and being determined as one of the alternatives in the vector control strategies.The bacilli were tried to be isolated from mosquito larvae, soil and water of various mosquito larval habitats surveyed in several areas of Yogyakarta Special Territory, Central Java and EastJava. A number of 549 isolates was obtained from 203 total samples collected. Tests of pathogenicity of all isolates against early fourth stage larvae of Culex quinquefasciatus mosquito revealed the existence of 4 positive bacilli, namely B. pumilus, B. eereus and two new strains of B. sphaericus.Key Wards: spore-forming bacilli -entomopathogens - B. pumilus B. cereus - B. sphaericus